AQP5-1364A/C polymorphism and the AQP5 expression influence sepsis survival and immune cell migration: a prospective laboratory and patient study. Issue 1 (December 2016) - Rump, Katharina; Unterberg, Matthias; Bergmann, Lars; Bankfalvi, Agnes; Menon, Anil; Schäfer, Simon; Scherag, André; Bazzi, Zainab; Siffert, Winfried; Peters, Jürgen; Adamzik, Michael
Abstract Background The C-allele of the aquaporin (AQP5) -1364A/C polymorphism is associated with decreased AQP5 expression but increased 30-day survival in patients with severe sepsis. AQP5 expression might affect survival via an impact on cell migration. Consequently, we tested the hypothesis that (1)Aqp5 knockout (KO) compared to wild type (WT) mice show an increased survival following lipopolysaccharide (LPS) administration, and that (2) AQP5 expression and the AQP5 -1364A/C polymorphism alters immune cell migration. Methods We investigatedAqp5 -KO and wild type mice after intraperitoneal injection of eitherE.coli lipopolysaccharide (LPS, serotype O127:B8, 20 mg/kg) or saline. Furthermore, neutrophils of volunteers with the AA-AQP5 or AC/CC-AQP5 - genotype were incubated with 10−8 M Chemotactic peptide (fMLP) and their migration was assessed by a filter migration assay. Additionally, AQP5 expression after fMLP incubation was analyzed by RT-PCR and Western blot. Moreover, migration of AQP5 overexpressing Jurkat cells was studied after SDF-1α-stimulation. We used exact Wilcoxon–Mann–Whitney tests; exact Wilcoxon signed-rank tests and the Kaplan–Meier estimator for statistical analysis. Results Fifty-six percent ofAqp5 -KO but only 22% of WT mice survived following LPS-injection. WT mice showed increased neutrophil migration into peritoneum and lung compared toAqp5 -KO mice. Target-oriented migration of neutrophils was seen after 0.5 h in AA-genotype cells but only after 1.5 h in AC/CC-genotype cells, with a threefold lower migrating cell count. AQP5 overexpressing Jurkat cells showed a 2.4 times stronger migration compared to native Jurkat cells. Conclusion TheAQP5 genotype may influence survival following LPS by altering neutrophil cell migration. Trial registration DRKS00010437. Retrospectively registered 26 April 2016